SISTEM PENGAIRAN OTOMATIS MEDIA TANAM HIDROPONIK MENGGUNAKAN SENSOR KELEMBABAN UDARA - Syarif Hidayatulloh; Fahmi Alwi Rifa’i; Rangga Ziancy Prasetya (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2020)
Population growth has led to a reduction in urban agricultural land. With the development of technology, the agricultural sector is also experiencing growth in farming patterns without soil media known as hydroponics. Hydroponics requires watering through pipes run by manually operated electric pumps. Human resources are needed to standby to operate it. Do not rule out the possibility, humans can be negligent and cause the water system is disrupted so that plants die. Making a pump active automatically is a way to reduce the occurrence of these problems. This automatic pumping system will be controlled by a microcontroller to irrigate plants automatically and can meet the required nutrient sources. An ATMega16 microcontroller is used that is programmed to analyze the input and output signals as needed. The input is a DHT11 sensor that is used to measure temperature and humidity, while the output is a water pump to irrigate all pipes. The output is also equipped with a 16x2 LCD which functions to display information on temperature and humidity. With the automatic irrigation system in hydroponic plants can save energy and facilitate the work in caring for plants with hydroponic growing media.